Screening of the Yeast yTHC Collection Identifies Essential Host Factors Affecting Tombusvirus RNA Recombination - Serviene, Elena (American Society for Microbiology, 2006)
RNA recombination is a major process in promoting rapid virus evolution in an infected host. A previous genome-wide screen with the yeast single-gene deletion library of 4,848 strains, representing ∼80% of all genes of yeast, led to the identification of 11 host genes affecting RNA recombination in Tomato bushy stunt virus (TBSV), a small model plant virus (E. Serviene, N. Shapka, C. P. Cheng, T. Panavas, B. Phuangrat, J. Baker, and P. D. Nagy, Proc. Natl. Acad. Sci. USA 102:10545-10550, 2005). To further test the role of host genes in viral RNA recombination, in this paper, we extended the screening to 800 essential yeast genes present in the yeast Tet-promoters Hughes Collection (yTHC). In total, we identified 16 new host genes that either increased or decreased the ratio of TBSV recombinants to the nonrecombined TBSV RNA. The identified essential yeast genes are involved in RNA transcription/metabolism, in protein metabolism/transport, or unknown cellular processes. Detailed analysis of the effect of the identified yeast genes revealed that they might affect RNA recombination by altering (i) the ratio of the two viral replication proteins, (ii) the stability of the viral RNA, and/or (iii) the replicability of the recombinant RNAs. Overall, this and previous works firmly establish that a set of essential and nonessential host genes could affect TBSV recombination and evolution.